Clinical, radiological, and pathological features of minute pulmonary meningothelial-like nodules and diffuse pulmonary meningotheliomatosis - Li, Naijian; Quan, Sicui; Liu, Qin; Xie, Zhiling; Wang, Qiong; Wang, Nian; Wang, Jinlin (Frontiers in Medicine, 2023)
Background: Minute pulmonary meningothelial-like nodules (MPMNs) and diffuse pulmonary meningotheliomatosis (DPM) are both rare lung diseases that involve the proliferation of cells of meningothelial origin in the lungs. However, few studies have focused on both the clinical, pathological and radiologic features of MPMNs and DPMs.The clinicopathological data of 167 cases diagnosed as MPMNs and 13 cases diagnosed as DPM in the China National Center for Respiratory Medicine were examined. Based on clinical data, CT image and morphological features, this study analyzed the similarities and differences between MPMNs and DPM.The detection rates of MPMNs and DPM were 1.9% and 0.15%, respectively.DPM patients were all females (100% vs 79.4%, P = 0.066), had a younger age (51.4±7.7 vs 57.9±8.5, P < 0.01), and had higher pulmonary function (P < 0.01 or P < 0.05) compared to MPMNs. The chest CT of DPM patients showed diffuse groundglass opacities nodules measuring 2.0 to 8.0 mm in diameter, with a number of nodules ranging from 40 to >600 per lung. There were no significant differences in nodule volume [28.0 (12.1, 65.1) mm 3 vs 28.7 (17.1, 48.9) mm 3 , P = 0.451] and CT values [-646.8 (-732.5, -514.5) Hu vs -588 (-674, -480) Hu, P = 0.215] between MPMNs and DPM. MPMNs are characterized by reactive hyperplasia pulmonary nodules, which can be solitary or multiple.Conclusions: This study suggests that there are many different characteristics between patients with MPMNs and DPM. The limited findings challenge the notion that DPM is a rare subtype of MPMNS.